MANAGING CROSS-CULTURAL RESEARCH PROJECTS IN EDUCATION: BRIDGING SOCIOLOGICAL PERSPECTIVES AND METHODOLOGICAL APPROACHES - Tuerah, Paulus Robert; Watania, Rietha; Suma, Elfira Yesy; Tuturoong, Yunita; Maukar, Merry Emilya Christine; Sumual, Tinneke Evie Meggy (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
This study explores the management of cross-cultural research projects in education, focusing on bridging sociological perspectives and methodological approaches. It aims to address the challenges and potential applications of cross-cultural research to promote inclusive education in diverse cultural settings. The study employs a qualitative approach using a literature review method, analyzing data from journals, books, and policy documents published between 2015 and 2022. Findings reveal three key aspects: the significance of sociological perspectives in understanding cultural influences on learning, challenges in managing cross-cultural research methodologies, and the potential application of research findings in curriculum development and teacher training. Sociological theories such as structural-functionalism and conflict theory provide insights into cultural dynamics, while methodological challenges highlight the need for adaptive strategies and international collaboration. This study recommends integrating research findings into practical educational policies to foster inclusivity and cultural competence. Teacher training programs and culturally responsive curricula are crucial to achieving these goals. Future research should focus on developing frameworks that bridge theory and practice, ensuring the sustainability and scalability of cross-cultural education initiatives. By addressing the complexities of cross-cultural education, this study contributes to the development of equitable and inclusive educational systems, preparing students to thrive in a globalized world.